Development and perspectives of the deposit insurance system worldwide - Zorčić Ksenija; Janković Miloš (Bankarstvo, 2022)
The history of the development of the deposit insurance system is quite long. There are a large number of different systems operating in the world that have changed over time, adapting to the circumstances in the environment. In any case, deposit insurance has become a central component of the financial safety net in most countries. The subject of this paper is an analysis of the development of the deposit insurance system throughout history, a comparative analysis of the organisation, functions and mandate of deposit insurers, with an emphasis on the importance of the deposit insurance system for preserving the country's financial stability. In addition, this paper aims to point out the importance of lessons derived from financial crises, which, above all, emphasised the need for financial system reforms and the creation of effective protection systems.